I am getting very frustrated with this problem as it seems no matter what happens the x's cancel out. If anyone could help me solve this I would greatly appreciate it.
Follow Math Help Forum on Facebook and Google+
Originally Posted by mushufasa11 I am getting very frustrated with this problem as it seems no matter what happens the x's cancel out. If anyone could help me solve this I would greatly appreciate it. Take natural logs: ln(2) + 3x = ln(4) + 5x rearrange: 2x = ln(2) - ln(4) = ln(2/4) = ln(1/2) so: x=(1/2) ln(1/2) = ln(1/sqrt(2)). RonL
Thanks a lot man. This is what I was doing before when taking the natural logs. (3x)(ln2) = (5x)(ln4) Leaving it as a product, rather than adding. I guess I didnt understand the property lne^x = x. thanks again
View Tag Cloud